2007
DOI: 10.1192/pb.bp.106.012336
|View full text |Cite
|
Sign up to set email alerts
|

Roles of general adult psychiatrists in follow-up clinics

Abstract: Aims and MethodCore features of New Ways of Working include concentrating on service users with complex needs, acting in a consultative role and carrying out interventions that are timely rather than routine. In this service-mapping exercise a retrospective analysis of 150 case notes was performed to evaluate clinical activity in general adult out-patient clinics and to attempt to measure the complexity of the workload.ResultsAnalysis of care programme approach (CPA) level revealed that 40% of patients were no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2009
2009
2010
2010

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…As recent work has shown that the level of intervention provided could differ between 'complex' and 'routine' patients (Mehta et al, 2007), a larger study might be needed to control for diagnosis. The findings on the prevalence of need identifies the range of problems that older people with enduring mental illness present to community mental health services, which differs significantly from their younger counterparts.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As recent work has shown that the level of intervention provided could differ between 'complex' and 'routine' patients (Mehta et al, 2007), a larger study might be needed to control for diagnosis. The findings on the prevalence of need identifies the range of problems that older people with enduring mental illness present to community mental health services, which differs significantly from their younger counterparts.…”
Section: Discussionmentioning
confidence: 99%
“…To make the survey more representative, this included both those under the community team and those seen at the out-patient department only. A recent study showed that these two groups of patients could need different levels of intervention provided between 'complex' and 'routine' patients (Mehta et al, 2007). Of the 77 people identified, 75 were interviewed (2 were untraceable) and their psychiatric keyworker was also interviewed separately.…”
Section: Methodsmentioning
confidence: 99%
“…Morer ecentlyt he European WorkingT imeD irectivesh avel imited junior doctors' working hoursm eaning that they arel essa vailablef or such,a rguably, inappropriate duties like the routine monitoringo fC lozapine patients (Harrison2 007).A lso,t he wayi nw hich Consultant Psychiatristsw orkh as been under reviewi nr ecent years, and it is suggested that current workingp racticesa re not in line with the 'New Ways of Workingi nM ental Health'i nitiative (Department of Health 2005;Mehta et al 2007).S ervice usersn ow expect moref romt heir health servicew ithm oret imew iths taff to 'participate in decision-makinga se qual partners' in regards to theirt reatment options (Harrison2 007: 471).W iths uchd emands on current practicesi ti sn ot surprisingt hat Clozapine clinicsa re identified as areas which could particularlybenefitfromnon medicalprescribing, utilisingthe speciale xpertise of the nursing staff (National PrescribingC entre2 005).I nf actL eppard( 2008) identifies Clozapine clinics as 'anexcellent exampleofarolefor asupplementaryprescriber in mental health' (p.164).…”
Section: Current Serviceprovisionsmentioning
confidence: 99%